A THE INFLUENCE OF CUSTOMER EXPECTATIONS ON BANK SERVICE PERFORMANCE AND BANK CUSTOMER SATISFACTION AND ITS EFFECT ON CUSTOMER TRUST - Zaenal Aripin; kosasih; vip Paramarta (KRIEZ ACADEMY : Journal of development and community service, 2023)
Beckground: The banking industry has experienced rapid development in recent years. Competition among banks has intensified, and to maintain a competitive advantage, it is important for banks to understand customer expectations, improve their service performance, and gain high customer satisfaction and customer trust. Aims: This study aims to analyze the influence of customer expectations on bank service performance, bank customer satisfaction, and how this influence impacts customer trust. The background of this study is based on the importance of improving customer satisfaction and customer trust in today's highly competitive banking industry. Research Method: The research method used in this study is a literature study. Various relevant literature sources, including scientific journals, books, and related research reports, were analyzed. This study analyzes and synthesizes the findings in the literature to identify the relationship between customer expectations, bank service performance, bank customer satisfaction, and customer trust. Results and Conclussion: The results show that customer expectations have a significant influence on bank service performance. When customer expectations are met, bank service performance tends to be better. In addition, bank service performance also has a significant influence on bank customer satisfaction. When bank service performance increases, bank customer satisfaction also increases. Furthermore, bank customer satisfaction also has a positive impact on customer trust in banks. Contribution: The contribution of this research is to provide a better understanding of the relationship between customer expectations, bank service performance, bank customer satisfaction, and customer trust. This research can serve as a reference for companies in the banking industry to improve their bank service performance, so as to meet customer expectations, increase customer satisfaction, and strengthen customer trust in the long run.